Pengaruh Metode Direct Instruction Terhadap Pengucapan Kata Siswa Disabilitas Fisik Kelas IV di SDLB YPAC Jember - Rofi' Udin; Dedy Ariyanto; Angger Timansah (Educatio, 2025)
This research aimed to examine the effect of the Direct Instruction method on word pronunciation skills in a fourth-grade student with physical disabilities at SDLB YPAC Jember. The research employed a single-subject methodology that includes an A-B model. The participant was a fourth-grade student, identified by the initial S, who has a physical disability. This study consisted of two phases: a baseline step consisting belonging to five sessions without any intervention, and an intervention phase spanning ten sessions using the Direct Instruction method. Data were collected through practical word pronunciation tests and analyzed descriptively, focusing on both within-phase progress and comparisons between phases. The results showed a noticeable improvement in the student’s pronunciation ability. During the baseline phase, the student’s average pronunciation score was 65%, which increased to 80% after the intervention. This 15-point improvement indicated a positive trend. Furthermore, the overlap percentage between the two phases was only 20%, demonstrating a considerable effect of the Direct Instruction approach to the student’s pronunciation skills. In conclusion, the Direct Instruction approach proved successful at enhancing word pronunciation intended for students who have physical disabilities. Which is therefore recommended as an alternative instructional strategy for special education teachers to support the development of students' verbal communication skills.